Performance of expanded non-invasive prenatal testing for fetal aneuploidies and copy number variations: A prospective study from a single center in Jiangxi province, China - Zou, Yongyi; Feng, Chuanxin; Qin, Jiawei; Wang, Xinrong; Huang, Tingting; Yang, Yan; Xie, Kang; Yuan, Huizhen; Huang, Shuhui; Yang, Bicheng; Lu, Wan; Liu, Yanqiu (Frontiers in Genetics, 2023)
To evaluate the performance of expanded non-invasive prenatal testing (expanded noninvasive prenatal testing, NIPT-Plus) in screening for fetal chromosomal abnormalities includes aneuploidies and copy number variations, a total of 23,116 pregnant women with a singleton pregnancy were recruited for NIPT-Plus. Screening positive results were verified by karyotype analysis and chromosomal microarray analysis after amniocentesis. A total of 264 pregnancies (1.14%) were positive results as predicted by NIPT-Plus, including 233 aneuploidies and 31 copy number variations. Following genetic counseling, 233 (88.26%) pregnant women underwent invasive prenatal diagnosis and 136 were verified as true positives, comprising 72 common trisomies (T21, T18, T13), 47 sex chromosomal abnormalities two rare autosomal aneuploidies (RATs) and 15 copy number variations The positive predictive value for common trisomies, SCAs, RATs and CNVs were 68.57%, 68.12%, 6.67% and 51.72%, respectively. Pregnant women with screen-positive results for common trisomies have higher rates of invasive prenatal diagnosis and pregnancy termination than those with positive results for SCAs, RATs, and CNVs. NIPT-Plus showed a good performance in detecting common trisomies, SCAs and also contributed to detecting pathogenic CNVs, but higher accuracy was required in the detection of RATs. In summary, this study provides a reference for the clinical application of NIPT-Plus for screening fetal chromosomal abnormalities in this region. Therefore, we suggest that NIPT-Plus could be widely used in clinical screening for fetal chromosomal abnormalities in combination with prenatal diagnosis and genetic counseling.